Pragmatic Functions of Code-Switching in Kaleb J’s Song “It’s Only Me" - Deaphenia Dordia Josanis Hia; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the pragmatic functions of code-switching in an Indonesian bilingual pop song, drawing on translanguaging theory as its primary analytical framework. Focusing on how systematic alternation between Bahasa Indonesia and English contributes to emotional expression and narrative organisation. Despite the growing presence of bilingual lyrics in Indonesian popular music, previous studies have largely concentrated on structural classification rather than pragmatic meaning. Addressing this gap, the study aims to identify, classify, and interpret instances of code-switching as deliberate communicative strategies. Employing a descriptive qualitative research design, the official song lyrics were segmented and analysed through structural classification and pragmatic discourse analysis, informed by translanguaging theory. The findings reveal that all instances of code-switching occur inter-sententially and follow a consistent verse–chorus pattern. Specifically, all switches occur at section boundaries, with Bahasa Indonesia dominating verses and the bridge, while English is used exclusively in the chorus. Bahasa Indonesia is used to convey intimacy and emotional vulnerability, while English functions to express emphasis, universality, and poetic appeal, together shaping the song's emotional progression and reinforcing its bilingual artistic identity. The study concludes that code-switching in Indonesian pop music is pragmatically motivated and artistically integral, highlighting bilingual lyrics as purposeful communicative acts rather than stylistic ornamentation. This study contributes to sociolinguistics and discourse analysis by demonstrating how bilingual song lyrics constitute intentional, meaning-oriented communicative texts.